PENGARUH KOPLEKSITAS TUGAS DAN LOCUS OF CONTROL TERHADAP KEPUASAN KERJA AUDITOR (Studi di kantor akuntan publik (KAP) HABIB BASUNI DAN HERYADI Surabaya) - Abdul Navir Bil’id Bafadal; Nur Diana; Junaidi Junaidi (Universitas Islam Malang, 2021)
The aims of this study are: 1) to analyze the effect of task complexity and locus of control on auditor job satisfaction. 2) Analyzing the effect of task complexity on auditor job satisfaction and 3) Analyzing the effect of locus of control on auditor job satisfaction. This research is included in explanatory research, because this study aims to test a theory, using a population of 35 auditors based on the Public Accounting Firm (KAP) Habib Basuni and Heryadi Surabaya. The data analysis technique used multiple linear regression analysis. Based on the output of the research and discussion that has been carried out, the following conclusions can be drawn: 1) There is an effect of task complexity and locus of control on auditor job satisfaction, by using increased task complexity and locus of control, auditor job satisfaction will increase. 2) The results of the analysis show that there is still an effect of task complexity on auditor job satisfaction, which means that by increasing the ability of employees to complete task complexity, the auditor's job satisfaction will increase. 3) There is a locus of control effect on the auditor's job satisfaction, is using an increase in locus of control, the auditor's job satisfaction will increase.Keywords: Task Complexity, Locus Of Control & Auditor Job Satisfaction